Anisotropic Mechanical Behaviour of Nickel Based Single Crystal Superalloy CMSX-4 for Prediction of Grain Recrystallization during Homogenization Heat Treatment Following Solidification. Issue 1 (1st January 2023) - Hazemann, E; Zhang, Y; Inal, K; Gandin, Ch A; Long, M; Niane, N T; Pinto Mora, A; Maguin, V; Leduc, M; Jaquet, V; Bellet, M
Abstract: In the present work, a methodology to identify parameters of an elastic viscoplastic behaviour law is presented. Orthotropic elasticity and Hill48 plastic anisotropy for as-cast CMSX-4 are considered. In order to obtain the corresponding parameters by inverse analysis, an experimental database is built by tensile/relaxation tests at constant temperatures between 800°C and 1200°C on specimens oriented along <001>, <110> and <111> directions at different strain rates. Tests are performed with a resistive heating machine, using infrared thermography and digital image correlation. The obtained mechanical behaviour is very dependent on specimen orientation at all tested temperatures. Recrystallization behaviour is also very relevant to the specimens' orientation.